Former Yugoslav Republic of Macedonia : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
This Selected Issues paper quantifies the short- and medium-term growth effects of major ongoing highway and railway projects in the Former Yugoslav Republic of Macedonia. A standard neoclassical growth model is augmented with public capital to capture both demand and supply-side effects of public infrastructure investments. The calibrated model suggests that the four ongoing highway and railway investments of 2-3 percent of GDP annually for 2014-18 are likely to raise the growth rate of real GDP by 0.5 percentage points on average for each year in 2014-20. Enhancing public investment efficiency can increase growth effects up to 0.8 percentage points.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet